Social support as a mediator in the relationship between technostress or academic stress and health: analysis by gender among university students - Asensio-Martínez, Angela; Aguilar-Latorre, Alejandra; Masluk, Bárbara; Gascón-Santos, Santiago; Sánchez-Calavera, María Antonia; Sánchez-Recio, Raquel (Frontiers in Psychology, 2023)
To request participation in the study, the link to the anonymous survey was sent, complying with the regulations in force regarding data protection (Organic Law 3/2018, of December 5, on Personal Data Protection and guarantee of digital rights). Google's privacy conditions were observed, providing the link to the information and requesting prior approval as a requirement for participation in the study. Participants had to give their informed consent, being free to opt out of the survey at any time. The dissemination period took place during the months of March and April 2022.